(untitled) (Research, Society and Development, 2026)
Bronchiectasis is a chronic respiratory disease characterized by irreversible dilation of the bronchi, associated with recurrent infections and a significant impact on quality of life. In Brazil, hospital data indicate that the disease is more prevalent in regions with poorer socioeconomic indicators. This study aimed to analyze the profile of hospitalizations for bronchiectasis in the Northeast Region of Brazil between October 2020 and October 2025. This is an ecological, retrospective, and quantitative study based on data from the Hospital Information System of the Unified Health System (SIH/SUS), available at DATASUS, considering the ICD-10 diagnosis of bronchiectasis. The following variables were analyzed: state, year of care, gender, age group, type of care, and deaths. During the period analyzed, there were 5,355 hospitalizations for bronchiectasis in Brazil, with 2,285 (42.67%) in the Northeast Region, the highest national frequency. The states with the highest number of hospitalizations were Bahia (21.36%), Pernambuco (19.04%), Piauí (17.94%), and Ceará (17.72%). An annual fluctuation was observed, with a peak in 2023 (23.33%). There was a similar distribution between the sexes, and the most affected age group was children under 1 year of age (21.18%). Most hospitalizations were urgent (78.42%). There were 91 deaths, with a hospital mortality rate of 3.98%. It is concluded that bronchiectasis is an important cause of hospitalizations in Northeast Brazil, reinforcing the need for early diagnosis and strengthening of public policies on respiratory health.